The Relationships Between Appropriating Public Spaces and Temporal Experience: A Transactional Exploratory Study - Mehmet Karasu; Sevim Cesur (İstanbul Üniversitesi Sosyoloji Dergisi)
The aim of this study is (1) to examine how space appropriation takes place and (2) to explore the relationships between the differences in space appropriation and temporal experience. The sample consists of 14 participants (six females and eight males) in Van, Türkiye who were reached using the criterion sampling and snowball sampling methods. Semi-structured in-depth interviews were analyzed through a template analysis. The results show that space appropriation to consist of the sub-aspects of identification, meaning, emotion, ownership, familiarity, usage features, transformativeness, orientation, space rhythm, sociability, and physical environment, which are covered by the following four aspects of transactional unity: psychological processes, temporal qualities, social environment, and physical environment. The patterns of public space usage are shaped according to the orientations toward these spaces. These patterns were gathered under two themes: functionalists and emotionally attached individuals. When considering the relationships between appropriation and the perceived passage of time, time is perceived to pass slowly when appropriation functions with the role of increasing the density of experience per standard temporal unit. Time is perceived as passing quickly if appropriation functions with the role of reducing the intensity of experience per standard temporal unit. Time is perceived to flow normally (i.e., have synchronicity) when appropriation helps to keep the density of experience per standard temporal unit at a normal level. These results highlight appropriation to have a multifaceted and dynamic structure that allows for a variety of experiences. This also indicates appropriation to function according to the complex relationships among the four aspects of transactional unity.